A new model for the reduced form of purple acid phosphatase: Structure and properties of [Fe2BPLMP(OAc)(2)](BPh4)(2) - Yim, SH; Lee, HJ; Lee, KB; Kang, SJ; Hur, NH; Jang, HG (WILEY-V C H VERLAG GMBH, 1998)
[(FeFeBPLMP)-Fe-II-B-III(OAc)(2)](BPh4)(2) (1), a new model for the reduced form of the purple acid phosphatases, has been synthesized by using a dinucleating ligand, 2,6-bis [((2-pyridylmethyl)(6-methyl-2-pyridylmethyl)amino)methyl-4-methylphenol (HBPLMP). Complex 1 has been characterized by X-ray diffraction method as having (mu-phenoxo)bis(acetato)diiron core. Complex 1 was crystallized in the monoclinic space group C2/c with the following cell parameters: a=41.620(6) Angstrom, b=14.020(3) Angstrom, c=27.007(4) Angstrom, beta=90.60(2)degrees, and Z=8. The iron centers in the complex 1 are ordered as indicated by the difference in the Fe-O bond lengths which match well with typical Fe-III-O and Fe-II-O bond lengths. Complex 1 has been studied by electronic spectral, NMR, EPR, SQUID, and electochemical methods. Complex 1 exhibits strong bands at 592 Mn, 1380 nm in CH3CN (epsilon=1.0x10(3), 3.0x10(2)). These are assigned to phenolate-to-Fe-III and intervalence charge-transfer transitions, respectively. Its NMR spectrum exhibits sharp isotropically shifted resonances, which number half of those expected for a valence-trapped species, indicating that electron transfer between Fe-II and Fe-III centers is faster than NMR time scale. This complex undergoes quasireversible one-electron redox processes. The Fe-2(III)/(FeFeIII)-Fe-II and (FeFeIII)-Fe-II/Fe-2(II), redox couples are at 0.655 and -0.085 V vs SCE, respectively. It has K-comp=3.3x10(12) representing that BPLMP/bis(acetate) ligand combination stabilizes a mixed-valence (FeFeIII)-Fe-II complex in the air. Complex 1 exhibits a broad EPR signal centered near g=1.55 which is a characteristic feature of the antiferromagnetically coupled high-spin (FeFeIII)-Fe-II system (S-total=1/2). This is consistent with the magnetic susceptibility study showing the weak antiferromagnetic coupling (J=-4.6 cm(-1), H=-2JS(1). S-2) between Fe-II and Fe-III center.
Keywords: IRON-OXO PROTEINS; ELECTRON-PARAMAGNETIC RESONANCE; ACTIVE-SITE; BOVINE SPLEEN; CRYSTAL-STRUCTURE; PORCINE UTEROFERRIN; BINUCLEATING LIGAND; IRON(III) COMPLEX; REDOX PROPERTIES; BEEF SPLEEN